Student Verbal Aggression Henry Manampiring's Self-Control Perspective: (Case Study of Student PPA South Lubangsa Putri) - Ach Maimun; Zahrotul Jannah (STAI Syaichona Moh. Cholil Bangkalan, 2022)
This study aims to explain the verbal aggression of the southern PPA Lubangsa students from Putri Guluk-Guluk Sumenep in terms of Henry Manampiring's self- control. This becomes important to discuss because because of verbal aggression on students is something that should not happen by offering self-control techniques from Henry Manampiring's perspective as the latest contribution to psychology. This study uses qualitative field research that seeks to analyze a person's behavior in a certain situation or place in detail. The type used is descriptive-analytical to describe the factors of the students' inability to restrain their verbal aggression in everyday life from the perspective of Henry Manampiring with a psychological approach. The results obtained were verbal aggression aggression behavior that occurred in the various types of PPA Lubangsa Selatan Putri students, including satire, swearing, threats, slander, backbiting, Etc. Various forms of verbal aggression against students are influenced by the environment, either family or friends. Meanwhile, from the point of view of self-control, Henry's approach shows the inability of the santri to distinguish between what is within him and what is not within him, so that his anger is easily ignited and leads to verbal aggression. A concise, specific, accurate and factual abstract is required.